DESCRIPTION OF THE IMPACT OF SCHOOL WELL-BEING ON ADOLESCENT STUDENTS - Novita Maulidya Jalal (Nindikayla Institute, 2023)
The complexity of the school's role in the student learning process contains important elements that will encourage the fulfillment of these functions optimally. Welfare at school (school well-being) is a factor that contributes to the learning process at school. Problems with school wellbeing in high school students cover several aspects, namely aspects of having, loving, being, and health. This study aims to determine the impact of school wellbeing on adolescent students. This study used the library research method using 10 research journals related to the theme of school wellbeing in adolescent students. Based on the research results, it is known that school well-being in adolescent students can have an impact on students, including having a positive impact on student involvement with activities at school, student motivation in learning, student relations with their social environment are more positive, so that it can have an impact on reducing delinquency in adolescent students